Penerapan E-Flipbook Berbantuan Project Based Learning dalam Meningkatkan Keterampilan Menulis Teks Eksplanasi Siswa Kelas V - Arifani, Selda; Purwati, Panca Dewi (Jurnal Likhitaprajna, 2025)
Writing skills are an important aspect of learning at the elementary school level, especially in Indonesian Language lessons. However, fifth-grade students at SD Negeri 1 Panusupan, Purbalingga Regency, still face difficulties in writing texts that clearly and structurally describe natural and social phenomena. This problem not only impacts students' literacy abilities but also hinders the development of their creative attitudes in expressing ideas and understanding the phenomena in their environment. This study aims to determine the steps for implementing the E-Flipbook ”Grebeg Suro” with the assistance of the Project-Based Learning model to improve students' explanatory writing skills and simultaneously develop their creative attitudes through the TPACK and Contextual Teaching and Learning (CTL) approaches. This research uses a mixed-method approach, combining both quantitative and qualitative methods. Quantitative data were obtained through writing skill assessments using scoring rubrics, while qualitative data were collected through interviews regarding the implementation of the module. The results of the study show that the average student score is 81.1, with 65.4% of the 26 students reaching mastery. This indicates that the implementation of the E-Flipbook "Grebeg Suro" is quite effective in improving explanatory writing skills, though further research is needed.